2017
DOI: 10.3389/fpls.2017.01368
|View full text |Cite
|
Sign up to set email alerts
|

Amaranthin-Like Proteins with Aerolysin Domains in Plants

Abstract: Amaranthin is a homodimeric lectin that was first discovered in the seeds of Amaranthus caudatus and serves as a model for the family of amaranthin-like lectins. Though these lectins have been purified and characterized only from plant species belonging to the Amaranthaceae, evidence accumulated in recent years suggests that sequences containing amaranthin domains are widely distributed in plants. In this study, 84 plant genomes have been screened to investigate the distribution of amaranthin domains. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 46 publications
2
30
0
Order By: Relevance
“…This is in line with a recent study, in which amaranthin sequences were identified in 33 plant genomes. Here, a similar complex distribution pattern was also observed (Dang et al, 2017).…”
Section: Resultssupporting
confidence: 84%
“…This is in line with a recent study, in which amaranthin sequences were identified in 33 plant genomes. Here, a similar complex distribution pattern was also observed (Dang et al, 2017).…”
Section: Resultssupporting
confidence: 84%
“…In addition, a proliferative effect of amaranthin on human colon carcinoma cells has been documented [ 44 , 45 ]. Although amaranthins have been considered to be unique for the Amaranthaceae family for a long time, amaranthin-related sequences are present in 34 out of 84 screened plant genomes including ferns, lycophytes and gymnosperms [ 28 , 46 ]. Amaranthins occur as hololectins but several chimerolectins containing an amaranthin domain linked to an aerolysin toxin domain have also been reported [ 46 ].…”
Section: Plant Lectin Familiesmentioning
confidence: 99%
“…Our description of apple amaranthin-like lectins completes the recent description performed by Dang et al (2017), although it did not allow us to identify tri-agglutinin encoding genes. Surprisingly, all mono-agglutinin encoding genes escaped the automatic annotation pipeline used for GDDH13 annotation.…”
Section: Discussionmentioning
confidence: 51%